Safety and Feasibility of Outpatient Rehabilitation in Patients With Secondary Bone Cancer: A Preliminary Study. Issue 3 (16th July 2021) - Tabacof, Laura; Delgado, Andrew; Dewil, Sophie; Reis, Fabiana; Velar, Camila Molina; Corteline, Munique Egle Dona; Cecatto, Rebeca Boltes; Putrino, David; Imamura, Marta; Battistella, Linamara Rizzo; Moran de Brito, Christina May
Abstract : Background: Because of fear of skeletal complications, physicians often avoid referring patients with secondary bone cancer (SBC) to physical rehabilitation. However, there is little evidence on the risk of skeletal-related events (SREs) and pathological fracture (PF) during rehabilitation therapies. Objective: To determine the risk of PF following physical rehabilitation in people with SBC. Design: Single-group, single-centered interventional clinical trial. Setting: University-based outpatient rehabilitation clinic. Patients: Forty-eight patients with confirmed diagnosis of SBC were enrolled. Interventions: Participants were prescribed a multidisciplinary rehabilitation program. Participants and rehabilitation therapists were trained to detect and report symptoms that would indicate PF. Radiographs were used to confirm the presence of PF. Measurements: The primary outcomes were safety and feasibility of an outpatient rehabilitation program for patients with SBC. Safety was measured by the rate of SREs. Feasibility was measured by the ability to successfully complete the program. Secondary outcome measures included Short Form Health Survey (SF-36) and numeric rating scale (NRS) scores to assess pain intensity. Results: One PF was detected, which occurred outside of rehabilitation therapy. Two other SREs occurred, resulting in a total event rate of 11.8 for every 10 000 hours of exposure. There was a significant improvement in NRS (95% CI, 1.41-3.08, P < .001) and SF-36 measures (95% CI, 80.35-158.11, P < .001). Limitations: Twenty participants (42%) did not complete the rehabilitation program due to clinical complications or death. Conclusions: Rehabilitation interventions may not increase the risk of SREs or PF in patients with SBC. Further research is indicated to verify these findings.